АНТУН ФАБРИС И РИСТА ОДАВИЋ: ИЗМЕЂУ ПРИЈАТЕЉСТВА И САРАДЊЕ (Prilozi za književnost, jezik, istoriju i folklor, 2023)
The paper encloses five letters from the editor of the „Dubrovnik” newspaper, Antun Fabris, to his friend and associate Rista Odavić. The letters cover the period from 1895 to 1897. They contribute to a more precise reconstruction of their author’s biography, supplementing previous knowledge about the history of Serbian periodicals as well as the history of Serbs in Dubrovnik and their efforts to confirm their identity in that city and prevent the already started process of drowning their Roman Catholic component in the Croatian corps. The letters are stored in the State Archives of Serbia in Belgrade, in the legacy of Rista Odavić.